Kewenangan Pejabat Pembuat Akta Tanah dalam Proses Jual Beli Tanah - . Ermasyanti (KEADILAN PROGRESIF, 2012)
Process the switchover of land right have there [since away back, and usually arranged in customary law, principally Bold and Cash. Bold of its meaning in doing before public Functionary in charge and its meaning Cash is paid in cash. Become if price not yet keel, hence not yet can be conducted by a sales process, such sales have to be poured in pukka act which is made by PPAT as public functionary given by authority make the certain pukka act. Pursuant to above description it is important to know kewenangan of Functionary of Maker  Act of land in course of land;ground sales. Kewenangan of Functionary of Act of land Maker PPAT in purchasing and selling agreement of land is execute some of activity and registry with the duty of act making otentik as evidence have been done by a certain law deed hit the land right or Property of For Set of Mansions taken as base for registration of change of land registry data.